Bi‐Enzyme Sensor for Phenolic Compounds with Fluorescent Read‐Out. Issue 44 (20th September 2013) - Strianese, Maria; Zauner, Gerhild; Tabares, Leandro C; Tepper, Armand W. J. W.; De Martino, Franco; Pellecchia, Claudio; Aartsma, Thijs J.; Canters, Gerard W.
Abstract In this paper, the use of tyrosinase (Ty) from Streptomyces antibioticus, labeled with a fluorescent tag, in combination with soluble quinoprotein (PQQ‐containing) glucose dehydrogenase (s‐GDH) to measure trace amounts of phenols is explored. Proof of concept is provided by a series of experiments, which show a clear quantitative dependence of the response on the phenol concentration. One of the advantages of the detection system is that apart from a standard fluorimeter no further instrumentation is required.